2008
DOI: 10.1111/j.1365-2036.2008.03642.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: ertapenem for complicated intra‐abdominal infections

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
(96 reference statements)
1
16
0
1
Order By: Relevance
“…The five meta-analyses studying different antibiotic regimens for the treatment of intra-abdominal infections compared ertapenem with other antibiotic regimens, 50 clindamycin/aminoglycoside with b-lactam monotherapy, 55 ciprofloxacin/metronidazole with b-lactam based regimens, 65 aminoglycosides with other antibiotic regimens, 73 and meropenem with other antimicrobials. 79 Ertapenem was found to be as effective as other antimicrobials for the treatment of complicated intra-abdominal infections.…”
Section: Meta-analyses Focusing On Topics Other Than Antibiotic Prophmentioning
confidence: 99%
“…The five meta-analyses studying different antibiotic regimens for the treatment of intra-abdominal infections compared ertapenem with other antibiotic regimens, 50 clindamycin/aminoglycoside with b-lactam monotherapy, 55 ciprofloxacin/metronidazole with b-lactam based regimens, 65 aminoglycosides with other antibiotic regimens, 73 and meropenem with other antimicrobials. 79 Ertapenem was found to be as effective as other antimicrobials for the treatment of complicated intra-abdominal infections.…”
Section: Meta-analyses Focusing On Topics Other Than Antibiotic Prophmentioning
confidence: 99%
“…A non-inferiority design was selected for this randomised clinical trial because the study drugs have shown similar efficacy to standard ␤-lactam-based antimicrobial regimens [8][9][10]12,13,16]. …”
mentioning
confidence: 99%
“…The results of in vitro and clinical studies showed that the use of ertapenem did not decrease susceptibility of P. aeruginosa, Enterobacteriaceae or other gram-negative pathogens to carbapenems [7,12].…”
Section: Discussionmentioning
confidence: 98%